Impact of Surface Roughness on the Aerodynamic Efficiency of Wind Turbines: A New CFD-based Correlation - A. Bouhelal; M. N. Hamlaoui; A. Smaili (Journal of Applied Fluid Mechanics)
The aerodynamic performance of wind turbines is significantly influenced by the design of their blades, which are engineered with advanced aerodynamic airfoils. However, the effectiveness of these designs is compromised by environmental factors such as dust, corrosion, sand, and insects, leading to alterations in blade shape and surface integrity over the turbine's operational period. These changes reduce the aerodynamic efficiency of the turbines. To assess these detrimental effects, this study utilizes a 3D Computational Fluid Dynamics (CFD) model based on the exact blade geometry. A modified version of the universal logarithmic wall function was implemented to quantify the influence of surface roughness. Comparative analyses between clean and rough blade surfaces under varying wind conditions showed that surface degradation significantly impacts the efficiency of wind turbines. Specifically, the findings indicate that surface roughness can lead to a substantial decrease in power output, with losses potentially reaching up to 35% under tested conditions. Notably, this roughness effect exhibits a critical value of  , beyond which the impact of roughness becomes negligible. Based on these results, an exponential correlation has been proposed. This study suggests that maintaining smooth blade surfaces or minimizing roughness is crucial for optimal turbine performance, especially under high wind conditions.